Event‐triggered global trajectory tracking control of a quadrotor: Synthesis, simulations, and experiments. (2nd July 2021) - Zhu, Xuan‐Zhi; Casau, Pedro; Silvestre, Carlos
Abstract: This paper presents an event‐triggered controller that solves the problem of trajectory tracking for an aerial vehicle with thrust actuation in a single body‐fixed direction and full angular velocity actuation. Firstly, we design a globally stabilizing hybrid controller and then, using the framework of hybrid dynamical systems, we derive an appropriate event‐triggering mechanism for sampling actuation signals. We prove the global asymptotic stability of a zero tracking error set for the closed‐loop system. For practical implementation of the proposed event‐triggered controller on digital platforms, we restrict the event‐triggering condition and inflate the zero tracking error set to avoid Zeno solutions while achieving global asymptotic stability of the inflated set for the closed‐loop system. The results are illustrated by numerical simulations and further verified by experiments.